The confluence of financial literacy and fintech: A bibliometric and systematic study - Janjanam, Venkata Vara Prasad; A.V.V.S, Subbalakshmi. (Edelweiss Applied Science and Technology, 2025)
This study conducts a bibliometric analysis to explore the relationship between financial literacy and fintech by systematically reviewing the literature. The research method involved studying relevant literature, authors, and publications, as well as analyzing the terms "financial literacy" and "fintech" using a sample of 200 publications from the Scopus database (2017-2024). The research tool used was Biblioshiny, a web-based tool from the bibliometric package in R, and the 20 most influential publications were further examined to provide valuable perspectives on the current state of research. The findings suggest a need to shape the development of financial literacy and education policies and indicate that further in-depth data exploration is needed to guide researchers in identifying new research avenues within financial literacy and fintech. The study concludes that emerging economies significantly contribute to this field, evidenced by developing countries—especially China, India, and Indonesia—leading in publication volume, while Nigeria, Germany, and Lebanon have the highest citation impact. International collaboration analysis reveals that developed countries typically cooperate more, with China and Indonesia exhibiting the most robust collaboration networks.